ANALISIS PENDIDIKAN AKHLAK DALAM KITAB NASHAIH AL-'IBAD DAN URGENSINYA TERHADAP REMAJA DI ERA MILENIAL - Mohamad Samsul Hadi; Abdul Muhid (Universitas Yudharta Pasuruan, 2019)
The attitude of faith and loving God as the basis of moral education is essential to the lives of the teenagers, especially in today's millennial eras. The absence of both would be a damage factor for future generations due to the moral degradation caused. It is necessary to transform the values of moral education from an early age, starting from family, school to their society. This study analyzes the moral education in Nashaih al-'Ibad by Sheikh Nawawi al-Bantani. This research is a library research with a qualitative approach of various relevant literature materials. Data analysis techniques with inductive and deductive methods. The results of this study show that faith and loving God are fundamental basic moral education that is very important for teenagers in the millennial eras.